RNA-seq de novo Assembly Reveals Differential Gene Expression in Glossina palpalis gambiensis Infected with Trypanosoma brucei gambiense vs. Non-Infected and Self-Cured Flies - Hamidou Soumana, Illiassou; Klopp, Christophe; Ravel, Sophie; Nabihoudine, Ibouniyamine; Tchicaya, Bernadette; Parrinello, Hugues; Abate, Luc; Rialle, Stéphanie; Geiger, Anne (Frontiers in Microbiology, 2015)
Trypanosoma brucei gambiense (Tbg), causing the sleeping sickness chronic form, completes its developmental cycle within the tsetse fly vector Glossina palpalis gambiensis (Gpg) before its transmission to humans. Within the framework of an anti-vector disease control strategy, a global gene expression profiling of trypanosome infected (susceptible), non-infected, and self-cured (refractory) tsetse flies was performed, on their midguts, to determine differential genes expression resulting from in vivo trypanosomes, tsetse flies (and their microbiome) interactions. An RNAseq de novo assembly was achieved. The assembled transcripts were mapped to reference sequences for functional annotation. Twenty-four percent of the 16,936 contigs could not be annotated, possibly representing untranslated mRNA regions, or Gpg- or Tbg-specific ORFs. The remaining contigs were classified into 65 functional groups. Only a few transposable elements were present in the Gpg midgut transcriptome, which may represent active transpositions and play regulatory roles. 1,373 genes differentially expressed (DEGs) between stimulated and non-stimulated flies were identified at day-3 post-feeding; 52 and 1,025 between infected and self-cured flies at 10 and 20 days post-feeding, respectively. The possible roles of several DEGs regarding fly susceptibility and refractoriness are discussed. The results provide new means to decipher fly infection mechanisms, crucial to develop anti-vector control strategies.